The main international events on the 50th anniversary of the Antarctic Treaty - A. Fedchuk (Ukrainian Antarctic Journal, 2009)
The Antarctic Treaty was signed by twelve nations in Washington, DC on 1 December 1959. For the past five decades, the Antarctic Treaty has provided a firm foundation for ongoing international cooperation for “peaceful purposes only… on the basis of freedom of scientific investigation in Antarctica”. Building on the original fourteen Articles of the Antarctic Treaty, the Parties have developed a successful system of international governance for the continent and its surrounding seas. Growing from seven claimant and five non-claimant signatories, the Antarctic Treaty now engages 47 nations, which together represent nearly 90% of the global human population.